3x 2 x 4 )= 5 x 1 ) 3
![3x 2 x 4 )= 5 x 1 ) 3](https://d1avenlh0i1xmr.cloudfront.net/large/db81f035-09f8-45be-886d-476e2e153d2d/slide24.jpg)
- 3x 2 x 4 )= 5 x 1 )+ 3
- 2 3x 1 15 x 4 5 x 4 3
- 5x 3 3x 2 2x 4 x =- 1 3
- 3x 2 )- 4 x 2 )= 4 x 5 )+ 3 2x 1
- 5 3 x )- 2 4 3x )= 11 2 x 1
- 3x 2 )( x 4 )- 3 x 5 )( x 1 )= 0
- 3x 4 )( x 4 )+( 5 x )( 2x 2 3x 1
- 3x 4 x 3 6x 5 x 2 1
- 4 x 3 )- 5 x 2 )= 7 3x 1 )+ 29
- 3x x 2 4 )+ 2x 3x 3 5 x 1 find the solution
- H x )= 5x 3 3x 2 2x 4 x =- 1 3
- X 3 3x 2 5x 4 x 1
- 3x x 1 )- 4 x 5 )=( x 3 2 9